Pendampingan Legalitas Usaha NIB (Nomor Izin Berusaha) dan Sertifikat Halal Bagi Pelaku UMKM di Kelurahan Gentong - Muhammad Ridwan; Tristan Rokhmawan; Homsah Homsah; Rani Sugiyanti; Izza Afkarina (Karya Nyata : Jurnal Pengabdian kepada Masyarakat, 2024)
This article discusses the importance of business legality, especially in obtaining Business Identification Numbers (NIB) and Halal Certificates for Micro, Small and Medium Enterprises (MSMEs) in Gentong Village, Pasuruan. Gentong District has many MSMEs that play an important role in the local economy, but face challenges in understanding and managing business legality, which results in limited access to wider markets. This article highlights the mentoring program carried out using the Service Learning method, which involves direct interaction between academics, students and MSME actors. This program aims to increase the understanding and skills of MSME players in managing NIB and Halal Certificates, as well as overcoming bureaucratic obstacles which often become obstacles in managing business legality. Through this approach, MSME players are expected to be able to increase the competitiveness and sustainability of their businesses. This article also examines relevant theories, such as Legitimacy Theory, Social Capital Theory, and Market Access Theory, which support the importance of business legality in building reputation, expanding markets, and reducing legal risks. The results of this mentoring program show that with adequate business legality, MSMEs in Gentong Village are able to expand business networks, increase credibility, and access larger market opportunities, both at the local and international levels. Thus, business legality is not only an administrative fulfillment, but also an important business strategy for the growth and sustainability of MSME businesses amidst increasingly tight market competition.